PENGEMBANGAN FLASHCARD YANG MENGINTEGRASIKAN KEARIFAN LOKAL SEBAGAI MEDIA PEMBELAJARAN NILAI-NILAI PANCASILA DI LINGKUNGAN KELUARGA PADA FASE A DI SD - Hania Dwitri Fadhia; Destrinelli; Silvina Noviyanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Education plays an important role in national development. Pancasila Education in elementary school is essential for shaping students’ character and civic understanding, especially in applying Pancasila values in the family environment. However, learning is often teacher-centered and relies on conventional media, resulting in low student engagement and limited understanding. This study aims to develop a local wisdom-based flashcard learning media and determine its validity and practicality. This research used a Research and Development (R&D) method with the 4D model, consisting of Define, Design, Develop, and Disseminate stages. Data were collected through observation, interviews, validation sheets, and questionnaires. The product was validated by experts in language, material, and media, and tested through small and large group trials. The results showed high validity, with language validity at 100%, material validity at 70% (valid), and media validity at 90.18% (very valid). Practicality results were also high, with teacher responses at 90%, small group trials at 84%, and large group trials at 87.86%. These findings indicate that the developed flashcard media is feasible, practical, and effective in improving students’ engagement and understanding of Pancasila values in elementary school.